(untitled) (Mugda Medical College Journal, 2025)
A cross-sectional, descriptive study was conducted among the female garment workers in Dhaka, Bangladesh, to observe their occupational impact on their musculoskeletal systems and biomechanical risks. A total of 488 female garment workers were selected from 4 garment factories in 4 corners of the greater Dhaka industrial zone. Among them, two were large factories and two were small factories. Data were collected by face-to-face interviews and by direct observation using Rapid Upper Limb Assessment (RULA) in employee assessment worksheet. RULA data showed 98.98% of respondents are action level 4 or more. Among them, mild, moderate and severe pain were reported by 47.12%, 50% and 2.66% of the workers respectively Varying duration of pain symptoms were reported: <6 weeks by 61.88%, 6-12 weeks by 23.77% and >12 weeks by 14.14% of the participants. However, the majority of workers (88.32%) reported satisfaction with their jobs. 52% of the particupants were suffering from some forms of musculoskeletal diseases. An extremely high prevalence (92%) of musculoskeletal symptoms were found among the participants. Musculoskeletal symptoms were reported in the generalized body, lower back, neck, foot, ankle, knee, shoulder, wrist and elbow (45.2%, 34.5%, 29.4%, 17.1%, 15.9%, 12,7%, 11.1%, 7.5% and 4.4% respectively). The research urgently calls for immediate ergonomic improvements, comprehensive health education, and substantial policy reforms to better protect the health and rights of these workers. It emphasizes the need for stakeholders to create safer and healthier working conditions, thereby enhancing the sustainability of the garment sector and empowering its critical workforce. Mugda Med Coll J. 2025; 8(1): 36-42